Online Marketing in Bangladesh: A Descriptive Study in the Context of Some Selected Click and Mortar Businesses - Hassan, Md Kamrul; Momen, Md Abdul; Sultana, Seyama (Journal of Business and Technology (Dhaka), 2012)
Every business requires a good marketing mix to introduce, grow, and sustain in this highly competitive market economy. The day before yesterday marketers were rarely looking at online based marketing efforts, instead, they were just relaying on conventional marketing mix. With the presence of highly growing Internet users, relative low cost and easy going strategies, ‘online marketing’ is also becoming so crucial for every business hub. By getting the balance of offline and online advertising right, marketing mix will help provide everything firms need to gain leads, increase sales, improve customer retention, and rocket the company profits. The study has a comprehensive perspective and provides a bird’s eye view of the online marketing practice in Bangladesh. This discussion is extended with an examination of the studies that compare conventional marketing practices with the principles and rules of the online marketing world particularly the four major components of the traditional marketing mix in an online context. To understand the online marketing environment in the country a greater sense of the study has extended its overall views from both the consumers and business perspectives. This study provides an effort to understand the relationship between online marketing exercise and the area of business operation (international vs. domestic) as well as gives an idea why marketers use Internet in the country. And this paper concludes with the prime exercise of online marketing which is centralizing mostly for leveraging international business operations in Bangladesh. Keywords: Online Marketing; Online Marketing Mix; E-commerce; Click and Mortar Business DOI: http://dx.doi.org/10.3329/jbt.v5i2.9986 Journal of Technology (Dhaka) Vol. 5(2), July-December, 2010 150-165